Development Tourism Village of Conto Village Based on Local Wisdom and Community Empowerment - Dwi Yoso Nugroho; Joko Triyono (Ideas Publishing, 2022)
Conto Village which is located in Bulakrejo, Wonogiri Regency has a lot of potentials, especially in the field of local wisdom which is used as a supporter of the economic field for mutual prosperity. This article aims to find out the process of developing a tourism village through local wisdom and community empowerment in Conto Village by using the theory of the use of local wisdom as a tourist attraction and community-based tourism. This research is descriptive qualitative research with data collection techniques through interviews, observation, and documentation. The results of the study show that some of the local wisdom in Conto Village has become a tourist attraction in addition to the natural tourism offerings of Soko Langit and Gua Resi . Local wisdom is presented in the form of traditional performing arts such as rebana, angklung, kethek ogleng, and reog . In addition, there are educational tourism and the mingling of tourists into the daily activities of the village community. Community empowerment through homestay management, home industry in the form of handicrafts and culinary arts, as well as tourism managers who are members of Pokdarwis (Kelompok Sadar Wisata/Tourism Awareness Groups) as an effort to improve the welfare of the local community.